Alopecia areata incognita – An underrecognized entity masquerading as female pattern hair loss. - Soundarya, S.; Pooja, T.U.; Jayakar, T. (European Journal of Pediatric Dermatology, 2024)
Alopecia areata incognita is a particular variant of alopecia areata that presents with widespread hair loss without the classic patchy pattern. It is more frequent in the third and fourth decades and must be differentiated from female pattern hair loss and telogen effluvium. A case of diffuse alopecia areata in a 12-year-old girl simulating androgenetic alopecia and treated with tofacitinib was presented.